ANALISIS IMPLEMENTASI KEBIJAKAN PEMBINAAN PASAR RAKYAT BABADAN KABUPATEN SEMARANG - Kusuma Dayuninggar, Nawang; Nurcahyanto, Herbasuki; Marom, Aufarul (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2024)
The Semarang Regency Government has stipulated Semarang Regency Regional Regulation Number 2 of 2018 concerning Policies for the Arrangement and Development of People's Markets, Shopping Centers and Supermarkets. This regulation serves as a guideline in implementing policies for developing the Babadan People's Market in Semarang Regency, but its implementation has not yet run optimally. This research aims to analyze the implementation of the Babadan People's Market development policy in Semarang Regency and analyze the supporting and inhibiting factors. The method used in this research is descriptive qualitative with data collection through interviews and documentation. The results of the research show that the implementation of the Babadan People's Market development policy in Semarang Regency has not been fully implemented properly according to applicable regulations. The phenomenon of the right policy, right implementer, right process, right environment and right target has not run optimally. Supporting factors for implementing this policy are communication, resources and bureaucratic structure. Meanwhile, the factor inhibiting policy implementation is the disposition of the implementer. This research recommends that market managers be more assertive in controlling traders who violate regulations, implement zoning related to levies for traders, and collaborate between implementers and policy formulators in collecting data regarding potential levies.